Някои наблюдения върху представянето на спрежението на силните глаголи в учебни пособия по трите континентални скандинавски езика: част I – шведски език - Найденов, Владимир (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
This is the first part of a two-part article which discusses and contrasts the ways in which strong verbs are usually described in educational materials for the three Mainland Scandinavian languages as L2. The first part examines materials for Swedish. It demonstrates that in spite of a certain variation, Swedish strong verbs are generally distinguished more or less systematically from irregular ones and the regular patterns found in their conjugation are emphasised.
Keywords: strong verbs; Swedish; regularity; didactics